CAREER EDUCATION OPPORTUNITIES FOR CHILDREN WITH BEHAVIORAL PROBLEMS AT SCHOOL - Augustinienė, Aldona; Šimkienė, Greta; Stanišauskienė, Vilija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Researchers, analysing career education, note that although the topic has recently received a great deal of global interest and schools are actively working to modernize their career education system, however, it is still inconsistent (Surgėlienė, 2014; Falco, 2016; Ho, Sum, & Wong, 2018; Seward & Gaesser, 2018; Chuang, Lee, & Kwock, 2020; Keele, Swann, & Davie-Smythe, 2020; Yang & Wong, 2020; Gati & Kulcsár, 2021). Actually, most graduates are unsure about their future career decisions, tend to change their choices. In this context, there are doubts about the quality of career education in schools as the evaluation of career education at school reveals various vulnerable groups to whom this service is restricted due to various internal and external conflicts (Hu, Hood, Creed, & Shen, 2020; Xu, 2020). The analysis, based on the PRISMA 2020 (Page et al., 2021), aims to answer the questions 1) What are the main institutional (school) empowerment conditions that enable students to gain quality career education? 2) How to encourage students with behavioural problems to take advantage of these opportunities? The review of the research allowed to construct a conceptual framework of career education for children with behavioural problems at secondary school.